2014
DOI: 10.1111/echo.12790
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mechanics in Untreated Normotensive Patients with Type 2 Diabetes Mellitus: A Two‐ and Three‐dimensional Speckle Tracking Study

Abstract: Left ventricular deformation obtained by 3DE is significantly impaired in the type 2 DM patients. HbA1c is independently associated with LV mechanics that implies that early anti-diabetic therapy and normalization of the fasting glucose level and HbA1c could impede further cardiac damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 28 publications
5
28
0
1
Order By: Relevance
“…The multiple regression analysis indicated that FPG and HPP were significantly associated with all strain values. These results were in good agreement with many previous studies, which verify the negative effect of overall blood glucose level on myocardial strain in diabetic patients . The toxicity of high glycemia was closely correlated with a series of pathogenic disorders of diabetic cardiomyopathy, such as an increase in collagen and myocardial stiffness, excessive lipid accumulation, and aberrant glycosylation of myocardial contractile protein .…”
Section: Discussionsupporting
confidence: 92%
“…The multiple regression analysis indicated that FPG and HPP were significantly associated with all strain values. These results were in good agreement with many previous studies, which verify the negative effect of overall blood glucose level on myocardial strain in diabetic patients . The toxicity of high glycemia was closely correlated with a series of pathogenic disorders of diabetic cardiomyopathy, such as an increase in collagen and myocardial stiffness, excessive lipid accumulation, and aberrant glycosylation of myocardial contractile protein .…”
Section: Discussionsupporting
confidence: 92%
“…Namely, in the present study, hypertensive individuals with LVH have significantly higher blood pressure values, BMI and BSA, plasma glucose and triglycerides levels than participants with normal left ventricular geometry or left ventricular concentric remodelling. Our study group previously has shown that all these cardiovascular risk factors are associated with impairment of 2DE and 3DE left ventricular mechanics independently of LVH [18,19], which could partly explain the lack of statistically important difference in left ventricular deformation between individuals with normal left ventricular geometry and concentric remodelling, who have similar cardiovascular risk profile. In addition, these groups are of similar age, whereas individuals with concentric, dilated and concentric-dilated LVH were significantly older, which also could be the reason for similar left ventricular mechanics between normal left ventricular geometry and concentric remodelling left ventricular individuals.…”
Section: Discussionmentioning
confidence: 73%
“…The correlation between different left ventricular geometry patterns and impaired 2DE and 3DE strains, independent of age, BMI, SBP level and left ventricular mass, was determined by multivariate logistic regression [odds ratio (OR) and 95% confidence interval (95% CI)]. Considering the fact that guidelines regarding cut-off values for 2DE and 3DE strains are still missing, we used data from meta-analysis and large population study [18,19]. Intraobserver and interobserver variability for 2DE and 3DE left ventricular mechanical parameters were analysed in 20 study participants using interclass correlation coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…The role of hypertrophy was limited to the LV concentric pattern and did not consider other forms, such as simple remodeling or eccentric hypertrophy, in the hypertensive disease . Elevated fasting glucose and glycated hemoglobin have previously been shown to be associated with an increase in LV untwisting rate in normotensive subjects . Findings such as this suggest that various risk factors may exert similar effects on the LV diastolic untwist that we considered as an adaptive mechanism in our study to avoid the increase in LV filling.…”
Section: Discussionmentioning
confidence: 91%